IMPLEMENTASI PENERAPAN METODE PEMBELAJARAN DISKUSI PADA GURU PENDIDIKAN AGAMA ISLAM DENGAN JUMLAH PESERTA DIDIK YANG SEDIKIT DI SDN 107411 LAU REMPAK - Alamsyah Alamsyah; Nur Fridayasha; Riska Angelina (Jurnal Bilqolam Pendidikan Islam, 2023)
This study also aims to explore the implementation of the application of learning methods to teachers of Islamic religious education with a small number of students at SDN 107411 Lau Rempa, and at the same time understand its impact on the quality of learning and motivation of students and to find out how the efforts made by teachers of Islamic religious education in applying learning methods even with a small number of students at SDN 107411 Lau Rempa. This research uses a qualitative approach and case studies as research methods. Data were obtained through interviews and observations of Islamic religious education teachers with a small number of students at school. The results showed that the implementation of the application of learning methods to Islamic religious education teachers with a small number of students at school could help improve the quality of learning and students' learning motivation. However, this implementation also faced several obstacles, such as a lack of resources and lack of support from the school. Therefore, support is needed from various parties, including school principals, teacher boards, and parents, so that the implementation of the application of learning methods for Islamic religious education teachers with a small number of students can run smoothly and effectively.